The Use of Sorts in Algebraic Specifications - Mosses, Peter D. (DAIMI Report Series, 1992)
Algebraic specification frameworks exploit a variety of sort disciplines. The treatment of sorts has a considerable influence on the ease with which such features as partiality and polymorphism can be specified. This survey gives an accessible overview of various frameworks, focusing on their sort disciplines and assessing their strengths and weaknesses for practical applications. Familiarity with the basic notions of algebraic specification is assumed.